Oral proficiency level required by the Main Call Centers in El Salvador, 2011-2012 - Alberto Acosta, Arely; Alvarez Umaña, David Alexander; Sánchez Gómez, Priscila Saraí; Zepeda de Laínez, Gilma Delfina; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2012)
Nowadays, Call Centers have become a booming industry in our country. El Salvador is considered as one of the main locations of choice for big companies due to its low operational and labor costs. As a matter of fact, Call Centers have fast spread in the country over the last few years, and they are being considered as one of the best contributors in the economic growth in El Salvador and still foreseen to be helping the country in the coming years. Call Centers in El Salvador provide both Inbound (inquiries, help desk, technical support, payments, order taking, complaints, assistance, among others) and outbound (telemarketing, telesurvey, telecollection, sales, among others). These are all being completed or accomplished via phone, fax, e-mail, chat and web tools. The industry rapidly grows every year, providing society with better job opportunities and salary improvement expectations just by being fluent in the English Language, and this new industry catches the attention of people Learning English as a Second Language (ESL) encouraging them to improve their Oral Proficiency in the English Language in order to become a Call Center agent. However, not all the applicants have the opportunity to achieve a position as a call center representative. There is a big inquiry about ESL students having no scope of lading in a Call Center position due to their lack of Oral fluency in the language. The findings of this research look forward to identify what is the Oral Proficiency level required by the main Call Centers in our country and what areas should be improved to make this process a lot easier for aspirants to be integrated into this competitive market
Anexos
Tesis -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- Enseñanza; Adquisición de segundo lenguaje; Call Centers en El Salvador; Dominio del lenguaje oral